Remote Patient Monitoring: A Paradigm Shift in Digital Health and AI-Driven Care - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Remote Patient Monitoring: A Paradigm Shift in Digital Health and AI-Driven Care The global healthcare landscape is at a critical juncture, grappling wi...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Medical Ethics; Patient Care